Heart rate variability after isocaloric exercise bouts of different intensities - Parekh, A.; Lee, C. M. (Medicine & Science in Sports & Exercise, 2005)
Purpose: To examine cardiac autonomic modulation, via heart rate variability (HRV), after exercise bouts at 50% (LO) and 80% (HI) of [latin capital V with dot above]O2 reserve ([latin capital V with dot above]O2R).